Ocular pathology - Yanoff, Myron; Fine, Ben S. (Philadelphia : Mosby, 2002)
Presents authoritative information on every aspect of eye pathology from basic principles through the full range of specific conditions
System requirements : Windows; Intel Pentium processor, Microsoft Windows 95 or higher, 32 MB of RAM, 12 MB of available hard-disk space, Acrobat Reader 4.05 or higher (version 4.05 included on CD)
System requirements : PowerPC processor, Mac OS version 8.6 or higher, 32 MB of available hard-disk space, Acrobat Reader 4.05 or higher (version 4.05 included on CD)
Keywords: Eye Diseases